2014
DOI: 10.12693/aphyspola.126.782
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Structural Properties of Bismuth Doped ZnO Thin Films by Sol-Gel Method: Urbach Rule as a Function of Crystal Defects

Abstract: Bismuth (Bi) doped zinc oxide (ZnO:Bi) thin lms were prepared on glass substrates by solgel spin coating technique using homogeneous precursor solutions, and eects of Bi doping on the structural and optical properties of ZnO were investigated. The crystalline of ZnO lms shifted from polycrystalline nature to amorphous nature with Bi doping. The plane stresses (σ) for hexagonal ZnO and ZnO:Bi crystals were calculated according to the biaxial strain model. The Urbach rule was studied as a function of non-thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…On the other hand, the steepness parameter (σ) decreases with increasing Co 2+ concentration. The behavior of E U and σ is reasonable and it is in good agreement with those reported in the literatures for other materials [48]. Doping ZTS crystals with cobalt leads to increasing the defects and forming localized states.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…On the other hand, the steepness parameter (σ) decreases with increasing Co 2+ concentration. The behavior of E U and σ is reasonable and it is in good agreement with those reported in the literatures for other materials [48]. Doping ZTS crystals with cobalt leads to increasing the defects and forming localized states.…”
Section: Resultssupporting
confidence: 90%
“…The Urbach tail energy (E U ) is proportional to temperature (Temp.) by the following relation [48]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it was observed that the FWHM values of the (100) and (002) diffraction peaks increased with the increase in the doping ratio. These results also verify that Bi atoms are successfully doped into the ZnO lattice and cause lattice expansions in the ZnO crystals [19,24]. The crystallite size of the samples was determined by the Debye-Scherer formula given in Eq.…”
Section: Resultssupporting
confidence: 64%
“…The exponential absorption tails for photon energies of sub‐band gap of both crystalline and amorphous materials have been widely studied, and the E u , which is related to the steepness of the tails (the so‐called Urbach's tails), has been defined as a function of the temperature ( T ) and the degree of crystal disorder of the material. As shown in previous works, the non‐thermal component to the disorder, clearly observed especially in the case of non‐crystal semiconductors, could be extracted from the optical absorption coefficient equation obtaining a value related to the absorption edge energy width.…”
Section: Composition/size/matrix Effectmentioning
confidence: 99%